Pengaruh Sudut Chamfer Terhadap Timing Melt Point Pada Penyambungan Material Mild Steel Menggunakan Las Gesek Rotari - Fahma Putri; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Teluk sirih feeder is one of few feeders of Bungus Padang substation (Gardu Induk Bungus Padang) with channel length of 30,6 kMS. The longer the length of a channel, the greater power losses and voltage drop occured in the channel. This study aims to evaluate and to reconfigure the system by reconstructing teluk sirih feeder in order to reduce or minimalize the power losses and voltage drop in teluk sirih feeder. Based on the results of the evaluation carried out through ETAP software simulation, the voltage drop of teluk sirih feeder is 18,995 kV and the power losses are 12,203 MW and 1268,111 MVAR. The voltage drop result doesn't meet the requirement set in SPLN No. 72 of 1978. In accordance to the evaluation result, a system reconfiguration was performed by reconstructing teluk sirih feeder with breaking the load and building new feeders. Based on the result of teluk sirih system reconfiguration carried out through ETAP software simulation, the voltage drop is 19,222 kV and the power losses are 12,287 MW and 1223,513 MVAR. The voltage drop result increases and meets the requirement set in SPLN No. 72 of 1978. Keyword : Distribution system, system reconfiguration, voltage drop